Implementation of the OHS-interRAI for regular oral health assessments by non-dental caregivers: focus group study using a SWOT analysis - Patricia Ann Ivonne Vandenbulcke; Johanna de Almeida Mello; Florence Marleen Paulien Piccart; Jan De Lepeleire; Emilie Schoebrechts; Anja Declercq; Dominique Declerck; Joke Duyck (BMC Public Health)
Abstract Background Oral health remains challenging in nursing home residents. The international Resident Assessment Instrument for Long-Term Care Facilities (interRAI LTCF) enables multidimensional geriatric assessment and care planning through Collaborative Action Points (CAPs), scales, and other outputs. The optimised oral health section for use within the interRAI instruments, OHS-interRAI, empowers non-dental caregivers to monitor and address oral health issues. This qualitative study explores caregivers’ experiences with the OHS-interRAI to guide its further optimisation and implementation. Methods Qualitative data were collected from non-dental caregivers (e.g., nurses, nurse aides) between February-November 2023 within a cluster randomised controlled trial comprising one control and two intervention groups. Focus groups, supplemented by observations, were conducted three months and one year after the training and implementation of the OHS-interRAI. Both intervention groups received e-learning. Additionally, intervention group 2 received on-site training. The control group continued using the existing oral health section. Strengths, Weaknesses, Opportunities, and Threats (SWOT) of the OHS-interRAI and its implementation were analysed and validated by the participants. Results Thirty-one caregivers were involved in six focus groups. The OHS-interRAI was valued for its comprehensive, accurate, and easy-to-perform assessment. CAPs were considered useful, though triggered frequently and not yet used in care planning. Implementation opportunities were mainly situated at policy and organisational levels. Threats included staffing-related issues, gaps in oral health knowledge and skills, team involvement and motivation, and dementia-related challenges. Nineteen caregivers were observed conducting 51 oral health assessments. All intervention group caregivers visually inspected residents’ mouth, averaging 5 min 48 s (± 3 min) per assessment, including introductory and conclusive acts. Assessment skills were sufficient, though infection control needed attention. Control group assessments lacked visual inspection and were sometimes completed without residents’ presence. Conclusions The OHS-interRAI enables non-dental caregivers to assess and monitor oral health in a feasible manner. Broader implementation and use in care planning require integration of the OHS-interRAI into the interRAI LTCF instrument. Key prerequisites include user-friendly software, involving more staff, training, protocols and guidelines for oral care and improved access to dental care. Incorporating dental hygienists into multidisciplinary teams and engaging residents and families offer additional opportunities to enhance oral health outcomes. Trial registration ClinicalTrials.gov NCT06536322-July 23, 2024.